THE EFFECT OF HYPNOTHERAPY ON THE LEVEL OF ANXIETY OF PREGNANT WOMEN IN THE THIRD TRIMESTER - Permatasari, Indah; Yulianti, Ria; Hidayah, Fika Nurul; Kumalasary, Diyanah (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2025)
In the third trimester of pregnancy, there are physical changes and side effects of pregnancy that make mothers worry, so pregnant women start to worry about the birth process. Hypnotherapy techniques can help relax the muscles so that the mother avoids anxiety and makes the mother calmer when facing childbirth. This research aims to determine the effect of hypnotherapy on the anxiety level of pregnant women in the third trimester. The research sample was 30 people, carried out from 15 May to 15 June 2023. This research is a quantitative research with a Quasi Experiment design with a one group pre test and post test design. The analysis method used was univariate and bivariate, analysis using the Paired Samples T-Test. The results of the study showed significant differences before and after hypnotherapy on pregnant women with a significance value of 0.000 0.05. In conclusion, there is an influence of hypnotherapy on the level of anxiety in third trimester pregnant women at PMB Indah Permatasari, 2023. The suggestion is that midwives can apply hypnotherapy as a complementary approach in an effort to reduce the level of anxiety in third trimester pregnant women in handling childbirth.